Critical energy deficit and mortality in critically ill patients - Marcia Carolina Siqueira-Paese; Diana Borges Dock-Nascimento; José Eduardo de Aguilar-Nascimento (Nutrición Hospitalaria)
Objective: We investigate the influence of caloric and protein deficit on mortality and length of hospital stay of critically ill patients. Methods: A cohort prospective study including 100 consecutive patients in a tertiary intensive care unit (ICU) receiving enteral or parenteral nutrition. The daily caloric and protein deficit were collected each day for a maximum of 30 days. Energy deficits were divided into critical caloric deficit (≥ 480 kcal/day) and non-critical caloric deficit (≤ 480 kcal/day); and in critical protein deficit (≥ 20 g/day) and non-critical protein deficit (≤ 20 g/day). The findings were correlated with hospital stay and mortality. Results: The mortality rate was 33%. Overall, the patients received 65.4% and 67.7% of the caloric and protein needs. Critical caloric deficit was found in 72% of cases and critical protein deficit in 70% of them. There was a significant correlation between length of stay and accumulated caloric deficit (R = 0.37; p < 0.001) and protein deficit (R = 0.28; p < 0.001). The survival analysis showed that mortality was greater in patients with both critical caloric (p < 0.001) and critical protein deficits (p < 0.01). The Cox regression analysis showed that critical protein deficit was associated with higher mortality (HR 0.25, 95% CI 0.07-0.93, p = 0.03). Conclusions: The incidence of caloric and protein deficit in the ICU is high. Both caloric and protein deficits increase the length of hospital stay, and protein deficit greater than 20 g/day is an independent factor for mortality in critical care unit.